2022
DOI: 10.1039/d2sc01379g
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the interplay between homogeneous and heterogeneous catalytic mechanisms in copper–iron nanoparticles working under chemically relevant tumour conditions

Abstract: The present work sheds light on a generally overlooked issue in the emerging field of bio-orthogonal catalysis within tumour microenvironments (TMEs): the interplay between homogeneous and heterogeneous catalytic processes. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 89 publications
2
36
0
Order By: Relevance
“…We investigated the reactivity of the CuFeS 2 /GSH system by using MS and 1 H NMR to monitor both GSH and GSSG. The initial concentration of GSH was set to 5 mM in order to mimic the intracellular environment. ,, We detected the product GSSG after 3 and 24 h of reaction by MS (detected ions: [M + H] + = 613 and [M + Na] + = 635) (Figure a). 1 H NMR analysis also confirmed both the generation of GSSG and the consumption of GSH.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We investigated the reactivity of the CuFeS 2 /GSH system by using MS and 1 H NMR to monitor both GSH and GSSG. The initial concentration of GSH was set to 5 mM in order to mimic the intracellular environment. ,, We detected the product GSSG after 3 and 24 h of reaction by MS (detected ions: [M + H] + = 613 and [M + Na] + = 635) (Figure a). 1 H NMR analysis also confirmed both the generation of GSSG and the consumption of GSH.…”
Section: Resultsmentioning
confidence: 99%
“…We then probed the byproduct generated in the reaction with GSH using 1,3-diphenylisobenzofuran (DPBF). Prior to studying the CuFeS 2 –GSH reaction, we evaluated whether DPBF was capable of reacting with H 2 O 2 or with • O 2 – , two potential byproducts of the GSH oxidation reaction. , Our results suggested that DPBF could not react with added H 2 O 2 either in the absence or presence of GSH (Figure S10a,b), but did with KO 2 , a source of superoxide anions (Figure S10c,d). Therefore, a decrease in DPBF absorbance present in a mixture of CuFeS 2 with GSH can be related to the generation of • O 2 – (Figure S11).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations